LIVED EXPERIENCES OF THE ABUSED ELDERLY - Acob, Joel Rey U (Public Health of Indonesia, 2018)
Aim: The study determined individual lived experiences of the abused elderly in the provinces of Leyte and Biliran.Methods: The study utilized qualitative phenomenology. Interviews are made and recorded, then later transcribed verbatim. Collaizi's method is used as method of analysis to obtain themes of the lived experiences of the ten abused key informants.Results: Based from results, most of the abused entities are female, widowed aging 6o to 65 years old, earning less than 2000 pesos per month and are dependently living in a nuclear family structure for 40 years. Based on their responses to the open-ended guide questions, key informants revealed emotional mistreatment being the most extensive type of abuse. Physical and sexual maltreatment are also evident amidst their old age. Family members and employers are the main identified perpetrators of the elderly. Bruises on most covered areas in their body, rope burns, torn undergarments, being touched without consent are some of the objective indicators of abuse. Themes such as family violence and workplace mistreatment are the most common form of abuse experienced.Conclusion: Based from the findings, it is recommended that the local government and concerned stakeholders to timely review existing rules protecting vulnerable adults especially its implementation.